The enhanced performance of a CeSiOx support on a Mn/CeSiOx catalyst for selective catalytic reduction of NOx with NH3. Issue 86 (31st August 2016) - Li, Wei; Guo, Rui-tang; Wang, Shu-xian; Pan, Wei-guo; Chen, Qi-lin; Li, Ming-yuan; Sun, Peng; Liu, Shu-ming
Abstract : A series of Mn/CeSiO x catalysts were prepared by the wet impregnation method and used for selective catalytic reduction of NO with NH3 . Abstract : A series of Mn/CeSiO x catalysts were prepared by the wet impregnation method and used for selective catalytic reduction of NO with NH3 . As can be seen from the experimental results, the Mn/CeSiO x catalyst with a Ce/Si molar ratio of 2/1 showed excellent low-temperature SCR activity, high N2 selectivity and excellent SO2 and H2 O tolerance. The relationship between the CeSiO x support and the SCR performance of Mn/CeSiO x (2 : 1) catalyst was investigated based on the characterization results of N2 adsorption, XRD, XPS, H2 -TPR, NH3 -TPD and in situ DRIFT. The strong interaction between Ce and Si resulted in the good dispersion of Mn species on the support; correspondingly, the redox ability and NH3 adsorption capacity were greatly enhanced. The results of in situ DRIFT study revealed that the NH3 -SCR reactions over Mn/CeO2 and Mn/CeSiO x (2 : 1) mainly obeyed both the E–R mechanism and the L–H mechanism. Furthermore, the formation of more Mn 4+ and chemisorbed oxygen greatly facilitates the oxidation of NO to NO2, as a result, promoting the low-temperature SCR performance of Mn/CeSiO x (2 : 1).